Mozart and friends. Music makes a difference - Mozart, Wolfgang Amadeus, 1756-1791.; Genius Products, Inc.; Warner Home Video (Firm) (Burbank, Calif. : Warner Home Video, 2002)
Mozart and friends introduces baby to colors, shapes, letters, numbers, animals, other babies and much, much more. These videos will stimulate the mind and delight your baby's senses.
Special features include: dolby digital ; jukebox featuring 16 classical selections ; interactive teaching activities ; magical music helper ; and more.
At head of title: Babygenius.
0 to 36 months.
DVD format ; single sided ; Dolby surround stereo.
Closed-captioned for the hearing impaired.
108377
Keywords: Infants -- Development -- Juvenile films; Intellect -- Juvenile films; Cognition in infants -- Juvenile films; Instrumental music -- Juvenile films; Orchestral music -- Juvenile films; Motion pictures in education; Video recordings for the hearing impaired; Music; Juvenile works; Children's films